1974
DOI: 10.1002/eji.1830040607
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibody response of primed rabbit peripheral blood lymphocytes to Group A variant streptococcal polysaccharide

Abstract: Peripheral blood lymphocytes obtained from rabbits at various times after a primary course of immunization with streptococcal Group A‐variant vaccines were successfully stimulated in vitro with this vaccine. Day 5 cultures contained about 81 % IgM and only 19 % IgG plaque‐forming cells, day 10 cultures contained only 38 % IgM and 62 % IgG plaques, and day 15 cultures contained predominantly IgG plaques (83 %) and far fewer IgM plaques (17 %). Concomitantly, IgM and IgG secretion into the media was shown. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In a previous study it was shown that de novo synthesized anti-Av-CHO antibody can be identified in culture supernates by immunoelectrophoresis and isoelectric focusing analysis (2). In the present paper the amount of antibody produced in 1-ml cultures was measured by a modified Farr technique (10).…”
Section: Clonotype 2 Analysis Of Antibody Produced In Microculturesmentioning
confidence: 78%
See 4 more Smart Citations
“…In a previous study it was shown that de novo synthesized anti-Av-CHO antibody can be identified in culture supernates by immunoelectrophoresis and isoelectric focusing analysis (2). In the present paper the amount of antibody produced in 1-ml cultures was measured by a modified Farr technique (10).…”
Section: Clonotype 2 Analysis Of Antibody Produced In Microculturesmentioning
confidence: 78%
“…Discussion It was the purpose of this study to investigate, in an in vitro system, the state of immunological memory of rabbits that had previously been hyperimmunized against streptococcal group polysaccharides. Previous work revealed a longlived memory persisting throughout the lifetime of the rabbit at the level of specific IgG clonotypes (1) which could also be triggered in vitro (2).…”
Section: Clonotype 2 Analysis Of Antibody Produced In Microculturesmentioning
confidence: 99%
See 3 more Smart Citations